Aspectos ambientais e sociais envolvidos na transmissão da L. chagasi no município de Parnamirim/RN - Lima, Iraci Duarte de (2009)
Visceral leishmaniasis hás adapted in the past 20 years to periurban and urban areas, and in Natal, Rio Grande do Norte, it became endemic. Thid study aimed to evaluate the environmental and social aspectsof Leishmania chagasi infection and its epidemiologic transmission chain in an urban, periurban and rural area of Parnamirim-RN. A study with three sections was conducted: Section 1: Sectional study of the human and canine infection by L. chagasi and its environmental and social determinants. Section 2: Observational longitudinal cohort to evaluate the dynamics of the canine infection. Section 3: Longitudinal study to evaluate the behavior of Lu. Longipalpis vector and the seasonal factors related to its dynamics. To include in the study the hauses were randomly selected and georreferenciated. Montenegro skin test was done in the human population and blood samples were collected for anti-Leishmania antibody detection. The canine population was examinated for L. chagasi infection by RIFI, ELISA and ELISA for rK39. An entomologic surveillance was monthly done with CDC light trapsin 10 houses of each locality. Quantitative and qualitative analyses was done using STATISC 6.0. Probality and prediction maps were done using ArcGis 9.0 model. In the human population L. chagasi infection was associated with the area of the hause, age, sex, population densyti, vegetation, kind of the floor of thr hause, water and resides destiny. In the canine population L. chagasi infection was associated with the breed, size, time of living in the hause, presence of dogs in the neighborhood, presence of horses and donkeys in the neighborhood, vegetation, kind of the floor and walls of the hause. The human infection was associated with canine infction only when analyzed taking into account the locality. In the prospective study, serum conversion and antibody lost observed in 30,8% and 22% of the animals examined, respectively. The human infection rate by L. chagasi was 24,6%, by the presence of anti-Leishmania antibody and 38,6% by the Montenegro skin test. The canine infection rate 32,5% by the presence of anti-Leishmania antibody. The vector Lu longipalpis showed an atypical behavior. These results indicate that environmental and social factors are important variables associated with L. chagasi infection in humans and canines, with punctual association of thr last two. Control measures of the infection on the studied points are necessary, in the aim to reduce the endemic focus of the disease in the study area. This research was carried out in a multidisciplinary involving the categories of: doctor, biologist, veterinarian, statistical, pharmaceutical and biochemical